Co-therapy in Open Dialogue: Transforming therapists’ self in a shared space - Lagogianni, Christina; Georgaca, Eugenie; Christoforidou, Dimitra (Frontiers in Psychology, 2023)
The present study aimed to explore co-therapists’ relationship and how therapists’ individual presence influences this relationship in Open Dialogue. Although co-therapy is key in Open Dialogue network meetings, the processes of that relationship remain largely understudied. The study applied thematic analysis to semi-structured interviews with twenty Open Dialogue trained therapists working in public and private sectors internationally. The results indicate that therapists are present in a meeting with their experiencing and professional self. Specific co-therapy processes allow co-therapists to attune to one another verbally and physically, creating a shared space that promotes new common understandings, shared responsibility and ultimately a transformation of each therapist’s self and practice. Trust between co-therapists seems to be a prerequisite for co-therapy to flourish. Results of the present study reveal a dynamic influence of co-therapy practice, in which co-therapy promotes a more dialogical personality and allows the therapists’ own transformation, which in turn enables common understandings and sharing of responsibility. Considering the growing interest in dialogical approaches and Open Dialogue trainings, trainers, supervisors and practitioners need to be aware of and attend to the dynamics of co-therapy relationship in order to care for themselves, their team and ultimately the networks they collaborate with.